Tortor Dance: Preserving Indonesian Culture - Puji Lestari; Lambok Hermanto Sihombing (Universitas Negeri Medan, 2022)
Indonesia is a multicultural country. It has many tribes, languages, rituals, and even traditional dances. One of the traditional Indonesian dances is Tortor. Batak Toba people usually perform this dance on a special occasion like wedding ceremonies. This study aims to discuss how the Tortor dance symbolizes the identity of the Batak people. In order to help the authors doing the analysis, the qualitative method was applied. To support the observation, the authors used Cultural Identity theory from Stuart Hall. The data was taken from Official Instagram account of Cultures and Tourism Office of Samosir @disbudparsamosir, @festbudayabatak and other literary works. The result shows that some posts in the above Instagram accounts attempted to portray how Batak people preserve their culture, Tortor dance.